Muscle activation patterns related to diabetic neuropathy in elderly subjects: A Functional Reach Test study. (February 2016) - Maranesi, E.; Di Nardo, F.; Rabini, R.A.; Ghetti, G.G.; Burattini, L.; Mercante, O.; Fioretti, S.
Abstract: Background: This study was designed to assess, in healthy elderly, non-neuropathic and neuropathic diabetic subjects, the activation patterns of the main muscles involved in the Functional Reach Test, a well-recognized method to identify elderly subjects at risk of balance impairments. Methods: Surface electromyographic analysis of Sternocleidomastoideus, Rectus Abdominis, Erectores Spinae at L4 level, Rectus Femoris, Hamstrings, Tibialis Anterior and Soleus was performed in 10 healthy, 10 diabetic non-neuropathic and 10 diabetic neuropathic subjects. Findings: Results showed that in every group the first motor is Tibialis Anterior, that is recruited before the start of the test. An earlier activation of Tibialis Anterior ( P  < 0.05) was detected in diabetic neuropathic (ON at − 24% of the test period), compared with healthy (− 11%) and diabetic non-neuropathic (− 13%) groups. A significant earlier activation of Sternocleidomastoideus and Rectus Abdominis was found in diabetic neuropathic group, only with respect to healthy subjects. No significant difference was found in Rectus Femoris, Soleus, Hamstrings an Erectores Spinae onset among the three groups. Interpretation: Results suggest a trend of diabetic neuropathic patients in earlier anticipation of the activation of the anterior body-muscles. In particular, the earlier onset of Tibialis Anterior is likely to be performed to adjust the movement timing and to compensate for the delay in the recruitment of the motor units. This anticipation might be involved in the altered postural control with increased balance impairment detected in diabetic neuropathic patients, and thereby it might also be proposed as an index of neuropathy, evidenced in a simple and non-invasive manner. Highlights: Activation patterns analysis of the main muscles involved in the Functional Reach Diabetics with and without neuropathy have been analyzed. Surface electromyography is a suitable tool to deepen the interpretation of the test. Analysis of balance disorders progression with the presence of diabetes and neuropathy